SISTEM REKRUTMEN DAN PROFESIONALISME PENDIDIK DI INDONESIA (Sebuah Catatan Dalam Perspektif Perbandingan Atara Negara) - Anggriati Ledu Ngaba (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2019)
Formal education is a conscious effort made by the Indonesian government to educate the nation's life in accordance with the mandate of the UUD 1945. This effort is carried out by teachers as the spearhead of implementing formal education that is regulated by the national education system. So that teachers are the determining factor for educational success and are required to have appropriate qualifications and be able to carry out education effectively and efficiently and achieve national education goals. But in reality education in Indonesia is still far from successful if it is reviewed from the results of the PISA and the National Examination. This is due to the fact that there are still many incompatible rules with things that happen in the field. In contrast to Indonesia, several countries such as Singapore, Japan, South Korea, Finland and Canada show the success of their education system through PISA results in the top 10 highest groups. The success of these five countries is proof of their consistency in a system of rigorous teacher selection and development is a top priority by upholding the standards and rules that apply from the center to the school level.